2008
DOI: 10.1371/journal.pbio.0060147
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-XL Inhibits Membrane Permeabilization by Competing with Bax

Abstract: Although Bcl-XL and Bax are structurally similar, activated Bax forms large oligomers that permeabilize the outer mitochondrial membrane, thereby committing cells to apoptosis, whereas Bcl-XL inhibits this process. Two different models of Bcl-XL function have been proposed. In one, Bcl-XL binds to an activator, thereby preventing Bax activation. In the other, Bcl-XL binds directly to activated Bax. It has been difficult to sort out which interaction is important in cells, as all three proteins are present simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
293
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(322 citation statements)
references
References 57 publications
26
293
0
1
Order By: Relevance
“…In one, BCL XL binds to an activator (tBID), thereby preventing BAX activation. In the second, BCL XL binds directly to the activated BAX resulting in preventing oligomerization (Billen et al, 2008). RT-PCR and Western blot assays revealed that hesperetin significantly down-regulated the expression of BCL XL mRNA and protein in PC-3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In one, BCL XL binds to an activator (tBID), thereby preventing BAX activation. In the second, BCL XL binds directly to the activated BAX resulting in preventing oligomerization (Billen et al, 2008). RT-PCR and Western blot assays revealed that hesperetin significantly down-regulated the expression of BCL XL mRNA and protein in PC-3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Following that sort of logic, David Andrews recently proposed the 'embedding together' model, which tries to incorporate elements from both the direct and indirect activation model to form a new hypothesis in which the pro-survival proteins promote survival both by inhibiting the BH3-only proteins (direct model) as well as Bax/Bak (indirect model) (Leber et al, 2007). In this model, membrane permeabilization does not occur until Bax/Bak insert multiple sequences into the mitochondrial outer membrane lipid bilayer (Leber et al, 2007;Billen et al, 2008). Bax undergoes a conformational change upon membrane interaction and then a second change triggered by truncated Bid or other activators.…”
Section: Bh3-only Proteins and Their Rolesmentioning
confidence: 99%
“…This activated integral form of Bax then recruits more cytosolic Bax in the process of homo-oligomerization. Pro-survival proteins, such as Bcl-xL, are proposed to perform two functions: sequestering the activators and also neutralizing the membrane-bound Bax to prevent them from homo-oligomerizing (functioning as a dominant-negative Bax molecule) (Billen et al, 2008). More work on these hypotheses will for sure test their merit.…”
Section: Bh3-only Proteins and Their Rolesmentioning
confidence: 99%
“…3,4 Notably, Bcl-xL binds proapoptotic Bax and Bak, which prevents these proapoptotic Bcl-2 members from forming pores that induce mitochondria outer membrane permeabilization (MOMP). [5][6][7] In response to DNA damage, the tumor suppressor p53 promotes apoptosis by inducing expression of Puma, which sequesters Bcl-xL, thereby promoting Bax/Bak-mediated MOMP. 8,9 The prototypical NF-κB transcription factor, p65/p50, is tightly regulated by the inhibitory protein IκBα, which sequesters this heterodimer in the cytoplasm by masking the p65 nuclear localization signal (NLS).…”
mentioning
confidence: 99%